(untitled) (Research, Society and Development, 2026)
Rural education presents specific challenges related to pedagogical organization, especially in the context of multigrade classrooms, in which a single teacher works with students from different grade levels. In this scenario, continuing teacher education becomes a central element for improving pedagogical practices and ensuring students’ right to learning. This article aims to analyze the importance of teacher education in multigrade classrooms in rural schools of the municipality of Mimoso do Sul, Espírito Santo, Brazil, based on the Lesson Study method as a strategy for professional development. This is a qualitative, bibliographic, and analytical study grounded in scientific literature addressing rural education, multigrade teaching, teacher education, and Lesson Study. The results indicate that Lesson Study contributes to strengthening collaborative culture, re-signifying lesson planning, and promoting more formative and contextualized assessment practices. It is concluded that the implementation of Lesson Study represents a relevant formative alternative for teachers working in multigrade classrooms, provided it is articulated with school management actions and public policies aimed at valuing rural education.